The Dilemma of Prohibition of Former Corruption Inmates Registering as Legislative Candidates (Law Research Review Quarterly, 2018)
This study aims to find out the direction of legal politics in Indonesia regarding the rules for prohibiting former corruption prisoners from registering as legislative candidates. Prohibition of former corruption prisoners registering as legislative candidates is contained in Article 7 paragraph (1) letter h draft of KPU Regulation (PKPU) nomination of members of DPR, Provincial DPRD, and Regency / City DPRD. However, the rules of the KPU are contradictory to Article 240 paragraph 1 letter g of the Election Law, where a former prisoner who has served a sentence of five years or more, may run for as long as the person announces that he has been a prisoner to the public. In fact corruption falls into extraordinary crimes, therefore the KPU plans to provide strict rules, but on the other hand these rules are still contrary to laws and other regulations.